Robert Penn Warren's All the King's men / - Bloom, Harold (Chelsea House Publ., 1987)
A collection of critical essays on Warren's novel
Keywords: Aufsatzsammlung; Warren; Robert Penn <1905-1989>; Warren; Robert Penn; All the king's men; All the king's men.; Geschichte; American literature; Politicians in literature; Politics and literature